Forensic procedures for facial-composite construction. Issue 4 (9th November 2015) - Fodarella, Cristina; Kuivaniemi-Smith, Heidi; Gawrylowicz, Julie; Frowd, Charlie D.
Abstract : Purpose: – The paper provides a detailed description of standard procedures for constructing facial composites. These procedures are relevant to forensic practice and are contained in the technical papers of this special issue; the purpose of this paper is also to provide an expanding reference of procedures for future research on facial composites and facial-composite systems. Design/methodology/approach: – A detailed account is given of the interaction between practitioner and witness for producing a facial composite. This account involves an overview of the Cognitive Interview (CI) and the Holistic CI (H-CI) techniques used to obtain a description of the face of an offender (target); the authors then describe how this information is used to produce a composite from five popular face-production systems: Sketch, PRO-fit, Electronic Facial Identification Technique (E-FIT), EvoFIT and EFIT-V. An online annex is also made available to provide procedural information for additional composite systems. Practical implications: – The work is valuable to forensic practitioners and researchers as a reference for interviewing techniques (involving a CI or an H-CI) and using facial-composite systems. Originality/value: – The authors provide an accessible, current guide for how to administer interviewing techniques and how to construct composites from a range of face-production systems.